2022
DOI: 10.3389/ti.2022.10335
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Early Graft Function Using the BETA-2 Score Following Clinical Islet Transplantation

Abstract: Little is known about how early islet graft function evolves in the clinical setting. The BETA-2 score is a validated index of islet function that can be calculated from a single blood sample and lends itself to frequent monitoring of graft function. In this study, we characterized early graft function by calculating weekly BETA-2 score in recipients who achieved insulin independence after single transplant (group 1, n = 8) compared to recipients who required a second transplant before achieving insulin indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, the TUNEL assay showed that more apoptotic cells were detected in T2D‐Ctrl islet grafts, which could be reduced by AAV‐PAX6 transduction (Fig 6F). Previous studies have found that loss of transplanted islets can be detected in the first few days after transplantation (Biarnes et al , 2002; Eich et al , 2007), while the early graft function is closely associated with long‐term transplantation outcome (Vantyghem et al , 2009; Lam et al , 2022). We, therefore, harvested the graft‐bearing kidneys 1 week post‐transplant and found that PAX6 replenishment enhanced the early graft survival by reducing cell apoptosis (Appendix Fig S7B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the TUNEL assay showed that more apoptotic cells were detected in T2D‐Ctrl islet grafts, which could be reduced by AAV‐PAX6 transduction (Fig 6F). Previous studies have found that loss of transplanted islets can be detected in the first few days after transplantation (Biarnes et al , 2002; Eich et al , 2007), while the early graft function is closely associated with long‐term transplantation outcome (Vantyghem et al , 2009; Lam et al , 2022). We, therefore, harvested the graft‐bearing kidneys 1 week post‐transplant and found that PAX6 replenishment enhanced the early graft survival by reducing cell apoptosis (Appendix Fig S7B).…”
Section: Resultsmentioning
confidence: 99%
“…For all these reasons, a substantial proportion of the islet graft becomes damaged and is lost due to apoptosis. Of note, clinical studies suggest that islet graft function plays a predominant role to determine the long‐term transplantation outcome (Vantyghem et al , 2009; Lam et al , 2022). Therefore, significant progress remains necessary to enhance islet potency and to reduce the early loss of islets after transplantation, which could have a major impact on the long‐term success of islet transplantation and the number of diabetic patients that could benefit from the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation